3(4m+5)=3m-3

Simple and best practice solution for 3(4m+5)=3m-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4m+5)=3m-3 equation:


Simplifying
3(4m + 5) = 3m + -3

Reorder the terms:
3(5 + 4m) = 3m + -3
(5 * 3 + 4m * 3) = 3m + -3
(15 + 12m) = 3m + -3

Reorder the terms:
15 + 12m = -3 + 3m

Solving
15 + 12m = -3 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
15 + 12m + -3m = -3 + 3m + -3m

Combine like terms: 12m + -3m = 9m
15 + 9m = -3 + 3m + -3m

Combine like terms: 3m + -3m = 0
15 + 9m = -3 + 0
15 + 9m = -3

Add '-15' to each side of the equation.
15 + -15 + 9m = -3 + -15

Combine like terms: 15 + -15 = 0
0 + 9m = -3 + -15
9m = -3 + -15

Combine like terms: -3 + -15 = -18
9m = -18

Divide each side by '9'.
m = -2

Simplifying
m = -2

See similar equations:

| 21x^2-13x=-8 | | 2(x-1)/6=3x-5 | | -3(2x-1)=11x | | 6n+4=1n-11 | | -23-11= | | -3+12=13x-5-12x | | 7/9=p+1/3 | | 54+.09m=38+.13m | | 5x/x-1+1/x=6 | | 1/6y^2=y-3/2 | | 33x^2-37x+10=0 | | 8(x+1)=16+8x | | 7n+4=-11 | | 12(t-3)+3t=5(3t+5)-8 | | c+2=5 | | 16x=4x | | -8-8(k+4)=-8k-40 | | P+1/4=-31/2 | | 1/8y^2=-y-2 | | SA=2Pirh+2B | | 6n+y=-11 | | 8(b-6)=-4(-3b+1) | | -1+20=m-1 | | 5((40-x)+7)+10(40-x)+25x=405 | | 2+2x/5+5-x/2=21/10 | | -5r+9=-6r | | 2/5y^2+7/5y=9/5 | | 33+729/(-72)*8 | | -5n=0+8 | | .445n+14.7=41.4 | | h(t)=-16t^2+96t+640 | | 4w-3w+2w=2.4 |

Equations solver categories